Prokineticin receptor 2 affects GnRH3 neuron ontogeny but not fertility in zebrafish - Ivan Bassi (Nature Portfolio, 2020)
Abstract Prokineticin receptors (PROKR1 and PROKR2) are G protein-coupled receptors which control human central and peripheral reproductive processes. Importantly, allelic variants of PROKR2 in humans are associated with altered migration of GnRH neurons, resulting in congenital hypogonadotropic hypogonadism (CHH), a heterogeneous disease characterized by delayed/absent puberty and/or infertility. Although this association is established in humans, murine models failed to fully recapitulate the reproductive and olfactory phenotypes observed in patients harboring PROKR2 mutations. Here, taking advantage of zebrafish model we investigated the role of prokr1b (ortholog of human PROKR2) during early stages of GnRH neuronal migration. Real-Time PCR and whole mount in situ hybridization assays indicate that prokr1b spatial-temporal expression is consistent with gnrh3. Moreover, knockdown and knockout of prokr1b altered the correct development of GnRH3 fibers, a phenotype that is rescued by injection of prokr1b mRNA. These results suggest that prokr1b regulates the development of the GnRH3 system in zebrafish. Analysis of gonads development and mating experiments indicate that prokr1b is not required for fertility in zebrafish, although its loss determine changes also at the testis level. Altogether, our results support the thesis of a divergent evolution in the control of vertebrate reproduction and provide a useful in vivo model for deciphering the mechanisms underlying the effect of PROKR2 allelic variants on CHH.